Qur’anic Contents in the Secondary School Curriculum of Bangladesh: A Critical Appraisal of the Selected Textbooks - Muhammad Shahidullah (Universiti Sains Islam Malaysia, 2024)
Matric : 4150242 (FPQS)-Restricted until November 2026